"Bacteriological Status of Pressure Sore - A Study of 50 Cases" - Hossain, SI; Khundkar, SH (Bangladesh Journal of Plastic Surgery, 2013)
Background of the study: Pressure sores are major cause of morbidity and mortality in the patients of the long term care facility. Infected pressure sores are very difficult to treat. Managing pressure sore needs care and expertise. Objectives: To study the bacteriological status of pressure sore by qualitative and quantitative culture and to find out the sensitivity pattern of the isolated bacteria to the various antibiotics. Methods: 50 patients were included in this study. Wound swabs were collected from pressure sore and deep tissue specimen sampled from pressure sore for quantitative culture in 1st and 3rd visit at 20 days interval. Patients with pressure sore were followed up for healing and their wound healing rate according to PUSH Tool 3.0 is correlated with the bacterial load in the pressure sore. Results were summarized in data table and analyzed. Results: Pseudomonas species were found to be most frequent bacterial isolate followed by E.Coli. Next leading isolated bacteria were Staph. Aureus and Proteus. Ceftazidime, Amikacin, Ciprofloxacin and Gentamycin showed higher percentage of sensitivity and organisms mostly resistant to Ampicillin,Amoxycillin, Co trimoxazole,Flucloxacillin, Ceftriaxone. Quantitative culture of the pressure sore revealed that 40.5% of the sore had bacterial load >105 CFU/ gm of tissue and 59.5% had bacterial load <105 CFU/gm of tissue on 1st visit. On 3rd visit quantitative culture of the pressure sore after 20 days showed decrease in frequency of >105 CFU/ gm of tissue to 21( 28.37%). No statistically significant decrease of bacterial load from 1st to 3rd visit noted. No significant difference in healing also noted in between two groups and in different bacterial species. DOI: http://dx.doi.org/10.3329/bdjps.v3i1.15002 Bangladesh Journal of Plastic Surgery 2012, 3(1): 19-23